How monocarpic is Agave? - Simcha, Lev-Yadun (Flora. Morphologie, Geobotanik, Oekophysiologie, 2017)
•The common belief that all Agave plants flower only once, is partly wrong.•The problem is the common misidentification of what an individual is.•Most Agave species are polycarpic clonal plants with a strong branch hierarchy.•The size/flowering time differences cause the mistake “Agave flowers only once”.•The correct classification is important for identifying the involved genes. The common belief that all Agave L. plants flower only once, i.e., are monocarpic, is partly wrong. The genus Agave is mostly composed of perennial polycarpic clonal plant species that commonly show a strong size and physiological hierarchy between the larger branches (rosettes) that flower once and die, and smaller or younger branches that may later reach a large size or age, flower, and die. The problem with classifying Agave life history is the common misidentification of what an individual is and this may result in mistakes in studying the genetic and molecular basis of monocarpy.